“Ich war als Neurotiker erkannt…” Illness, Suffering, and Pain in Hermann Hesse - V. SZABÓ, László (Anafora, 2023)
The paper examines the interrelated topics of illness, suffering, and pain in several narrative texts by Hermann Hesse, such as Taedium vitae, Gertrud, A Guest at the Spa, and The Steppenwolf. The analysis focuses on the relation between illness, geniality, and art, partly biographical, partly based on contemporary discourses on (psychogenic) illness and healing, as they were prefigured in Nietzsche and Freud. The paper also reveals connections between Hesse’s concept of illness as a psychogenic phenomenon and his understanding of art. Finally, psychologic and physiological processes of healing as described in A Guest at the Spa or The Steppenwolf are also considered.